Effectiveness of an Educational Program on Nursing College Student’s Knowledge about Preventative Measures of Irritable Bowel Syndrome in Al Basra University: Comparison study. - Atea , Maher A.; Ahmed, Sabah A. (International Journal of Psychosocial Rehabilitation, 2020)
Irritable bowel syndrome (IBS) is a common disorder characterized by abdominal pain and altered bowel habit for at least 3 months that is also characterized by abdominal discomfort associated with altered bowel function; structural and biochemical abnormalities are absent. The main aim of the study is to determine the Effectiveness of an Educational Program on Nursing College Student’s Knowledge about Preventative Measures of Irritable Bowel Syndrome in Al Basra University. A quasi experimental study design is carried out at the nursing college -university of-Basra through the period from December 8th, 2019 to June 3th, 2020. The program and instruments were constructed by the researcher for the purpose of the study. the purpose of the study. A non- probability purposive sample of (80) nursing students were divided into four groups divided into both stages(second and fourth); two of the study groups consisted of (40) students who were exposed to an instructional program and two of the control groups consisted of (40) students who were not exposed to the program. The study instrument is composed of four parts: Part I. The socio-demographic characteristics of the students, Part II. The general information about IBS, Part III. The protection from IBS, Part IV. The prevention from IBS. The validity of the study instrument was determined through a panel of (13) experts and the reliability of the instrument was determined through the Person correlation coefficient method. The analysis of the data used was descriptive statistics and statistical inferential, in order to find the differences between the study group and the control group. The study findings indicate that there are significant differences between pre and post-tests in the study group in overall III main domains regarding preventive measure of IBS. The study concluded that The program had an effect on the students’ knowledge of the study groups for both stages, the levels of knowledge improved from a weak level to a good level. The researcher recommends performing continuous educational programs for students regarding preventive measures for IBS to increase their level of knowledge regarding how to instruct patients how to deal with this syndrome, increase lectures time and number about IBS and takes lectures in more than one course